Synthesis and in Vitro Antiproliferative Evaluation of C-13 Epimers of Triazolyl-d-Secoestrone Alcohols: The First Potent 13α-d-Secoestrone Derivative - Johanna Szabó (Molecules, 2016)
The syntheses of C-13 epimeric 3-[(1-benzyl-1,2,3-triazol-4-yl)methoxy]-d-secoestrones are reported. Triazoles were prepared from 3-(prop-2-inyloxy)-d-secoalcohols and p-substituted benzyl azides via Cu(I)-catalyzed azide-alkyne cycloaddition (CuAAC). The antiproliferative activities of the products and their precursors were determined in vitro against a panel of human adherent cervical (HeLa, SiHa and C33A), breast (MCF-7, MDA-MB-231, MDA-MB-361 and T47D) and ovarian (A2780) cell lines by means of MTT assays. The orientation of the angular methyl group and the substitution pattern of the benzyl group of the azide greatly influenced the cell growth-inhibitory potential of the compounds. The 13β derivatives generally proved to be more potent than their 13α counterparts. Introduction of a benzyltriazolylmethyl group onto the 3-OH position seemed to be advantageous. One 13α compound containing an unsubstituted benzyltriazolyl function displayed outstanding antiproliferative activities against three cell lines.